Design and Analysis of Interactive Multimedia Online Physical Education Platform considering Moving Object Segmentation Algorithm - Yanle Hu; Jing Zhou; Bin Gao (Advances in Multimedia)
With the development of Internet technology, Internet plus education has become a new mode of changing traditional education methods. Therefore, online physical education has attracted more and more attention. This paper introduces the sports object segmentation algorithm, designs an interactive multimedia online sports education platform by combining the research needs of sports online education platform, and analyzes online sports education from three aspects, sports teaching management, sports teaching resources, and sunshine sports activities, in order to improve the quality of sports education and improve students’ learning interest. Simulation results show that the algorithm is effective and can support the analysis of interactive multimedia online physical education platform.